The Educational System of the Palestinian Minority in Israel ‘under Occupation’: Educational Autonomy as a Right for Minorities - Haj-Yehya, Nehaya Awida (Studia Edukacyjne, 2020)
One of the foundation stones of a democratic state is the granting minorities an autonomous educational system, so as to assure that the hegemonic group does not take over the learning contents that are important to the formation of a cultural-religious-national identity that meets the needs of these minority groups. This research study will examine the case of the Palestinian minority who are citizens of the democratic State of Israel and will attempt to examine the extent to which this right to an autonomous educational system is granted. Who decides the goals and contents of learning of the ‘Arab educational system’ in Israel? The research study will examine the degree of desire and realization of these unique needs. It was found in this research study that the Arab educational system in Israel is still controlled by the Jewish majority and the educational policy is determined from topdown, as expressed in the goals and contents of the studies.